Development of E-Modules Based on Multi-representations in Solid-State Physics Introductory Subject - Wafi Lutfiatun Nisa; Ismet Ismet; Nely Andriani (Berkala Ilmiah Pendidikan Fisika, 2020)
This study also aims to produce e-modules based on multi-representations in solid-state physics introductory subjects with good validity and practicality. The products produced are in the form of e-modules in the form of 3D flipbooks, including video, animation, sound, flash, and hyperlinks. This study uses the Rowntree development model. This model has three stages, planning, development, and evaluation stage. In the evaluation phase, Tessmer formative evaluation used, which consist of 5 stages, self-evaluation, expert review, one-to-one evaluation, small group evaluation, and field test. In the expert review stage, the average results of evaluations from experts obtained at 4.6 or 92.2% with a very valid category. The one-to-one evaluation stage found that the average result of the student questionnaire's impression on the use of teaching materials was 89%, with the category very practical. At the small group evaluation trial stage, the average score of the students' questionnaire assessment towards the use of teaching materials was 93.48% (very practical category). Based on the assessment that has been done, the e-module (electronic module) based on a multi-representation in solid-state physics introductory subject has been successfully developed with good validity and practicality.